The influence of the interaction between platform types and consumer types on the purchase intention of live streaming - Xie, Ying; Du, Kai; Gao, Peng (Frontiers in Psychology, 2022)
Under the background of the rapid development of live streaming shopping industry, diversified live streaming platforms have emerged one after another. This study aims to explore the interaction effect of platform types (live streaming embedded in e-commerce platforms/LSEEC vs. e-commerce integrated into live streaming platforms/ECILS) and consumer types (goal-driven consumers vs. recreational consumers) on purchase intention. To verify the effect, this study firstly conducted a laboratory experiment (Study 1), and then carried out a questionnaire survey through the Internet (Study 2). The results indicate that the interaction effect of platform types and consumer types exists (Study 1) and thinking patterns play a mediating role (Study 2): for goal-driven consumers, LSEEC platforms are more likely to stimulate their rational thinking and enhance their purchase intention; for recreational consumers, ECILS platforms are more likely to stimulate their emotional thinking and enhance their purchase intention. The findings expand the depth of research related to live streaming platforms, deepen the understanding of the thinking patterns in live streaming shopping decision-making, and have certain guiding significance for the strategic formulation of enterprises.